Hungarian Monitoring, 8 December 1988 . [Magyar rádiófigyelő], 1988. december 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev flies home from New York because of Armenian earthquake - Situation in Tallinn - How did NATO react to Gorbachev's announcement? - Polish, Swedish, Czechoslovak and Paris reactions to Gorbachev's speech - Over 50,000 fatalities in Armenian earthquake - President of France arrives in Prague Domestic Affairs: - Defense Minister thinks one quarter of Soviet troops stationed in Hungary could be affected by announcement of unilateral reductions in military force - Report on mayor of Vienna's Budapest trip - Signatures being collected in Józsefváros, Budapest, for the recall of Miklós Vida, district MP and vice-president of Parliament - Young Communist League (KISZ) and Alliance of Young Democrats (Fidesz) representatives meet for the first time in Budapest Economy: - "Emphasizing the important of quality will remain a dream as long as the forint is not convertible and we try to sell our products to Eastern Europe:" - Tamás Beck at the conference on quality - According to Swedish experts metallurgy can be made profitable in Hungary Külpolitika: - Az örményországi földrengés miatt Gorbacsov hazautazik New Yorkból - Tallinni helyzetkép - Hogyan reagált a NATO Gorbacsov bejelentésére? - Lengyel, svéd, csehszlovák és párizsi vélemények a Gorbacsov beszédről - Már több, mint 5o.ooo halálos áldozata van az örményországi fölrengésnek - Prágába érkezett a francia köztársasági elnök Belpolitika: - A honvédelmi miniszter szerint a hazánkban állomásozó szovjet csapatok egynegyedét érintheti a bejelentett egyoldalú haderő leépítés - Beszámoló a bécsi polgármester Budapesti látogatásáról - Aláírás gyűjtés indult a Józsefvárosban a választókörzet országgyűlési képviselőjének, a Parlament alelnökének, Vida Miklósnak a visszahívására - Budapesten először találkoztak a KISZ és a FIDESZ képviselői Gazdaság: - A minőség fontosságát mindaddig vágyálom hangoztatni, amíg a forint nem konvertibilis és termékeinket Kelet-Európába próbáljuk eladni - Mondta Beck Tamás a minőségi konferencián - Svéd szakértők szerint Magyarországon nyereségessé tehető a vaskohászat